X-ray fluorescence core scanning data of sediment core GeoB24011-1 - Westerhold, Thomas (PANGAEA, 2024)
X-ray fluorescence (XRF) core scanning data from gravity cores retrieved during RV SONNE Cruise SO272 generated at MARUM University Bremen. XRF scanning was done on the split surface of the sediment cores to obtain the elemental composition from Aluminium to Uranium in order to geochemically characterise the bulk sediment composition. Cores were scanned with XRF core scanner III at MARUM University Bremen 09.12.2020 – 15.12.2020 and 23.-27.08.2021 using three runs (10kV, 30 kV and 50 kV). The gravity cores were retrieved from the Labuan and Gaggatt Basin spanning Plio-Pleistocene to Eocene sediments.
Keywords: data; Gravity core; Kerguelen Plateau Sediment Drifts; RV Sonne cruise SO272; XRF core scanner data